A hydrodynamic lubrication model and comparative analysis for coupled microgroove journal-thrust bearings lubricated with water. (November 2020) - Xiang, Guo; Han, Yanfeng; Chen, Renxiang; Wang, Jiaxu; Ni, Xiaokang; Xiao, Ke
The novelty of this study is to develop a hydrodynamic lubrication numerical model for coupled microgroove journal-thrust bearings (or coupled bearings) under water-lubricated condition. In the present model, the continuity of the hydrodynamic pressure and the fluid field (or coupled hydrodynamic effect) at common boundary is considered to reveal the mutual effect between the hydrodynamic behavior of the journal bearing and the thrust bearing. The lubrication performances of the coupled microgroove bearing with three bottom shapes, i.e., isosceles triangle, right triangle, and left triangle, are studied comparatively. Additionally, the effects of the microgroove depth on the lubrication performances of the coupled bearing are discussed. The present study reveals that the coupled hydrodynamic effect generated by the coupled bearing can improve the lubrication performance for both the journal and the thrust bearing. The microgroove with left triangle bottom shape yields the optimal lubrication performance as compared to the other two. There is an optimal groove depth that generates the maximum load capacity and the minimum friction coefficient for both the journal and the thrust bearing.